PENINGKATAN KEMAMPUAN GERAK LOKOMOTOR MELALUI PERMAINAN LARI ESTAFET MODIFIKASI - WULAN, DWI SEPTI ANJAS (Jurnal Pendidikan Usia Dini, 2015)
Abstract. This study aims to determinan to increase locomotor skiil in early childhood Through game relay modification. The study was conducted on group B kindergarten with of sixteen children. This study action research by model Kemmis & Taggart. This research was conducted by using a provision of the cycle. Each cycle has four main activities: planning, action, observation dan refleksion. This research consist of two cycles, each cycle consist of 8 times in actions. Analysis of the data used quantitative and qualitative approaches. Analysis of quantitative data used descriptive statistics that compare the results obtained from the first cycle. While the analysis of qualitative data used analizing data from the field notes and interviews during the research by steps of data reduction, data display and data verivication. In the pre cycle persentage yield 47,08% after the act of the first cycle increased to 62,39% and 82,03% second cycle becomes. The results showed an increase locomotor skiils in aerly chillhood B gruop conducted through learning game relay modification. Keywords: Locomotor Skiils, Game Relay Modification